Analyzing Patent Information on Canning Technology for Food to Enhance Potential Industrial Development - Tommy Hendrix (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
Modern movement has many impacts from R & D results, which becomes a general issue enabling technology enhancement to enter market requirement, primarily from portfolio through patent analysis. A patent is an intellectual property right granted under the law to protect an invention toward infringement. From patent information occurs product technology, especially connected to process that influences growth and restructuring of industrial leverage to enhance the economics of a community. Canning technology for foods as the entity of industrial process captures and introduces the chance of potential, innovative, and efficient strategies for global knowledge from appropriate technology and offers the possibilities for implementation based on reducing tools specification, timing process, and operational budgeting. The purpose of this paper is to know the competition among the same product through the utilization patent database registered on WIPO fields with patent analysis. The method in this research is patent analysis using Innography software from online WIPO database as potential leading patent-issuing authorities with 1747 patent document that is registered. This study intended as a reference and recommendation in the information for product canning technology for food benchmarking, which tailor to the capabilities and capacity R & D results from differences in significance innovation development for commercial in market needs